Study on the Coordinated Development of Economy, Tourism, and Eco-Environment in Sanjiangyuan - Xiaohui Wang (Mathematical Problems in Engineering, 2022)
Sanjiangyuan region is located in the hinterland of Qinghai-Tibet plateau, covering an area of 30.25 square kilometers, with the total population of 556000 people, including Tibetans, constituting more than 90%. Since it is the source of the Yangtze River, Yellow River, Lancang River catchment area, biodiversity concentration, and a beautiful environment, known as the “Chinese water tower,” occupy an irreplaceable strategic position in national development. Although Sanjiangyuan region is blessed with unique natural landscape and rich tourism resources, its ecological environment has been seriously deteriorated due to long-term man-made destruction, backward economic development, and increasing poverty, which have seriously affected and restricted the survival and development of local ethnic groups. Since the 18th National Congress of the Communist Party of China, General Secretary Xi Jinping has repeatedly emphasized that “Lucid waters and lush mountains are invaluable assets.” China advocates harmonious coexistence between humans and nature and sticks to the path of green and sustainable development. At the 19th National Congress of the Communist Party of China, the rural revitalization strategy was clearly proposed, which includes not only industrial revitalization but also ecological revitalization. In this paper, the area belonging to Sanjiangyuan National Park is taken as the main research object. By constructing economic, tourism, and ecological environment (TEE) evaluation indexes, the coupling degree and coupling coordination degree models are established, and the data from 2000 to 2019 are measured. The relationship of the three indicators is analyzed, and corresponding proposals for its development are put forward, such as implementing ecological compensation mechanism to improve the level of ecosystem management; blending into ethnic cultural elements to create a unique tourist resort; paying attention to economic development quality, building energy conservation and emissions reduction green engine; Doing a good job in the top-level design of ecological economy, and promoting the coordinated development of various indicators, etc. We will focus on quality control of economic development and build green engines for energy conservation and emission reduction. We will do a good job in top-level ecological and economic design and promote coordinated development of various indicators.